Strategi Belajar Outdoor Bagi Anak PAUD - Susilowati, Retno (THUFULA, 2014)
Learning Strategies outdoor make kids can enjoy the funand really help the growth and development. A wide variety of areasthat exist in the outdoor play environment surrounded by natureare natural so that children can observe the objects around him.The most important point of the arrangement of the outdoor environmentis children get a unique experience. For example, the science that comes byitself naturally, that explores and observes with theirown hands. Children cansee the color change, holding the bark of a tree, hear the crickets or smell theair after it rains; the children use all their feelings to learn about their world.Noting the importance of the outdoor environment to support the growth anddevelopment of children then you should give serious consideration in thedesign and use of the outdoor play area.